The impact of coronavirus in Brazil: politics and the pandemic - Ponce, Daniela [UNESP] (Nature Publishing Group, 2020)
Brazil has been severely affected by the novel coronavirus. At a time when the country needs to concentrate on controlling and fighting the virus, President Bolsonaro has minimized the importance of the pandemic and focused on political battles.